Peptide serum markers in islet autoantibody-positive children - Von Toerne, Christine; Laimighofer, Michael; Achenbach, Peter; Beyerlein, Andreas; Gala, Tonia De Las Heras; Krumsiek, Jan; Theis, Fabian J.; Ziegler, Anette G.; Hauck, Stefanie M. (Diabetologia, 2017)
Aims/hypothesis: We sought to identify minimal sets of serum peptide signatures as markers for islet autoimmunity and predictors of progression rates to clinical type 1 diabetes in a case–control study. Methods: A double cross-validation approach was applied to first prioritise peptides from a shotgun proteomic approach in 45 islet autoantibody-positive and -negative children from the BABYDIAB/BABYDIET birth cohorts. Targeted proteomics for 82 discriminating peptides were then applied to samples from another 140 children from these cohorts. Results: A total of 41 peptides (26 proteins) enriched for the functional category lipid metabolism were significantly different between islet autoantibody-positive and autoantibody-negative children. Two peptides (from apolipoprotein M and apolipoprotein C-IV) were sufficient to discriminate autoantibody-positive from autoantibody-negative children. Hepatocyte growth factor activator, complement factor H, ceruloplasmin and age predicted progression time to type 1 diabetes with a significant improvement compared with age alone. Conclusion/interpretation: Distinct peptide signatures indicate islet autoimmunity prior to the clinical manifestation of type 1 diabetes and enable refined staging of the presymptomatic disease period.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Autoantibody-positive; Autoimmunity; BABYDIAB/BABYDIET; LC-MS/MS; Progression time; Risk score; Selected reaction monitoring; Targeted proteomic; Type 1 diabetes